The Process of Becoming an Activist: Identity Transformations in Autobiographical Narratives of Women with Disabilities in Poland - Kamila Albin (Przeglad Socjologii Jakosciowej, 2023)
This article reconstructs identity transformations that manifest themselves in the biographies of female activists with disabilities. The empirical material was collected through autobiographical narrative interviews. The author identifies key stages and turning points for these identity transformations. She also analyzes the role of significant others in the process of identity transformations and becoming an activist. The analysis of narratives of women with congenital disabilities demonstrates that the incorporation of disability as an element of individual self-definition is an important factor contributing to identity transformations. In the analyzed narratives, disability represents a biographical resource and, like identity, is processual in nature. Although it accompanies the individual from birth, it undergoes reinterpretations at different stages of life.